Литература русского зарубежья. 1920-1940 - Михайлов О. Н. (2000)
Экземпляры: аб. (2001) / Инвентарный номер: 43068 / Цена: / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: Л 64 / ГРНТИ: 17.82.82 / ББК: 83.3(2Рос=Рус)6